Understanding atmospheric aerosol particles with improved particle identification and quantification by single-particle mass spectrometry - Shen, Xiaoli; Saathoff, Harald; Huang, Wei; Mohr, Claudia; Ramisetty, Ramakrishna; Leisner, Thomas (Atmospheric measurement techniques, 2019)
Abstract. Single-particle mass spectrometry (SPMS) is a widely used tool to determine chemical composition and mixing state of aerosol particles in the atmosphere. During a 6-week field campaign in summer 2016 at a rural site in the upper Rhine valley, near the city of Karlsruhe in southwest Germany, ∼3.7×105<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="ecd9c994d0009e01f99b4b07902c042e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-12-2219-2019-ie00001.svg" width="55pt" height="13pt" src="amt-12-2219-2019-ie00001.png"/></svg:svg> single particles were analysed using a laser ablation aerosol particle time-of-flight mass spectrometer (LAAPTOF). Combining fuzzy classification, marker peaks, typical peak ratios, and laboratory-based reference spectra, seven major particle classes were identified. With the precise particle identification and well-characterized laboratory-derived overall detection efficiency (ODE) for this instrument, particle similarity can be transferred into corrected number and mass fractions without the need of a reference instrument in the field. Considering the entire measurement period, aged-biomass-burning and soil-dust-like particles dominated the particle number (45.0 % number fraction) and mass (31.8 % mass fraction); sodium-salt-like particles were the second lowest in number (3.4 %) but the second dominating class in terms of particle mass (30.1 %). This difference demonstrates the crucial role of particle number counts' correction for mass quantification using SPMS data. Using corrections for size-resolved and chemically resolved ODE, the total mass of the particles measured by LAAPTOF accounts for 23 %-68 % of the total mass measured by an aerosol mass spectrometer (AMS) depending on the measurement periods. These two mass spectrometers show a good correlation (Pearson's correlation coefficient γ>0.6) regarding total mass for more than 85 % of the measurement time, indicating non-refractory species measured by AMS may originate from particles consisting of internally mixed non-refractory and refractory components. In addition, specific relationships of LAAPTOF ion intensities and AMS mass concentrations for non-refractory compounds were found for specific measurement periods, especially for the fraction of org ∕ (org + nitrate). Furthermore, our approach allows the non-refractory compounds measured by AMS to be assigned to different particle classes. Overall AMS nitrate mainly arose from sodium-salt-like particles, while aged-biomass-burning particles were dominant during events with high organic aerosol particle concentrations.
Gesehen am 21.08.2019